THE CONSTRUCTION OF KNOWLEDGE SOCIOENVIRONMENTAL IN SPACE MANAGEMENT RURAL: THE CASE OF DERRUBADAS – RS - Dhonathã Santo, Rigo (Universidade Federal de Santa Maria – Santa Maria – RS – Brasil, 2018)
Inadequate occupation of rural areas and the intense exploitation of natural resources characterized by conflicting land use, as well as the divestiture process educational and productive rural population which is subjected, deepens social problems already identified at the end of the last century. The paper aims to study the complex reality of the rural municipality of Derrubadas, as an effort to build knowledge and analysis, identifying the landscaping design in the diversity of natural and social factors present, relatively homogeneous areas and the aspects socioenvironmental gifts in one of them. In the study we used methodological procedures and A construção do conhecimento socioambiental na gestão do espaço rural... Redes (St. Cruz Sul, Online), v. 20, nº 2, p. 283 - 307, maio/ago. 2015 284 techniques for qualitative and quantitative approaches. Was done using the analysis of secondary data, reading the landscape, interviewing qualified informants and the community involved, besides the construction of thematic maps using the software spring and physical-chemical analysis of water samples. As a result, is observed the uneven occupation of rural areas of the county, with a large concentration of its population in vulnerable rural areas , low in suitability for agricultural use, limited in terms of production and land. For the community studied, retirement and welfare benefit (family bag) are present in income of 75% of the families interviewed. The result of water analysis, virtually all sources remained outside the potability standards established by the Ministry of Health, particularly the presence of total and fecal coliforms. These results are strongly related to social conditions encountered in the community, where 42% of households do not have an indoor bathroom and 50% of the houses, waste products are designed the-sky-opened. Allied to this variable, the lack of environmental planning of areas, mainly springs region, contributing to worsening levels of contamination found and highlights the environmental problems of such a community.